Investigating Agile Adaptation for Project Development - Rajesh H. Kulkarni; P. Padmanabham; Manasi Harshe; K.K. Baseer; Pallavi Patil (Institute of Advanced Engineering and Science, 2017)
Agile methodologies adaptation in software companies is an accepted norm.Rapid application development and efficient deliverables being the premise. The changing business needs, cost effectiveness and timely delivery are catered to by agile methods. Different software development models are in the literature and also are being used by the industry. Few companies have adopted agile, few are gearing up for and few are in transition. We investigated agile presence in a software company.Project management is an evolving art with innovative methods being added up.The aim of this paper is to tease about project management challenges, agile, agile transition in companies and a comparison of conventional software engineering practices with agile process model.This paper takes stock of the current status of quality in software projects and to add on quality process improvement strategies. The results presented here are after a qualitative interview study with one cross function team using streamline development framework in agile development.